1982
DOI: 10.1017/s0305000900004967
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of epistemic and deontic meaning of modals

Abstract: Modal auxiliaries have an epistemic and deontic sense and range in strength, e.g. must propositions are stronger than may propositions. Children (ages 3; 0–6; 6) heard two contradictory modal propositions of varying strength. In the epistemic condition, the propositions concerned the location of a peanut. In the deontic condition, they were commands by two teachers about what room a puppet should go to. The child was to indicate which command should be followed. The general acquisitional rule was: the greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 4 publications
(5 reference statements)
5
65
1
4
Order By: Relevance
“…may vs. should) or mental verbs (e.g. know vs. think) in English by the age of four (Hirst & Weil, 1982;Moore, Bryant, & Furrow, 1989;Moore & Furrow, 1991;Papafragou, 1998 Still, it is possible that the present findings underestimate what Korean children know about linguistic evidentials. Specifically, the first of our linguistic tasks requires children to reason explicitly about the meaning of the morphemes -e and -tay in order to infer who might have produced an utterance containing them.…”
Section: Discussionmentioning
confidence: 61%
“…may vs. should) or mental verbs (e.g. know vs. think) in English by the age of four (Hirst & Weil, 1982;Moore, Bryant, & Furrow, 1989;Moore & Furrow, 1991;Papafragou, 1998 Still, it is possible that the present findings underestimate what Korean children know about linguistic evidentials. Specifically, the first of our linguistic tasks requires children to reason explicitly about the meaning of the morphemes -e and -tay in order to infer who might have produced an utterance containing them.…”
Section: Discussionmentioning
confidence: 61%
“…The majority of the children failed to reject a statement such as ''The cow may be in the pink box" when the statement was weaker than the available evidence (e.g., when the cow had to be in the pink box). However, when given a choice between may and has to versions of the same statement in the same context, children overwhelmingly chose the modal that was most appropriate based on the evidence available to the speaker (see also Chierchia et al, 2001;Hirst & Weil, 1982). In line with this evidence, the methodological account -but not the psycholinguistic account -predicts that Turkish learners' evidential comprehension should improve in the contrastive task of Experiment 3 compared to Experiment 2.…”
Section: Methodsmentioning
confidence: 95%
“…3 Third, the idea that a listener would reject a strong interpretation when it is provided seems unlikely. Many have shown (Hirst & Weil 1982;Moore et al 1990;Noveck et al 1995, Chierchia et al 2004) that children, at least, prefer stronger utterances over weak ones in the absence or presence of validating context. For example, Noveck et al (1995) showed how five-year-olds prefer to follow the advice of the speaker who uses has to over another who uses might when there is no way to determine which is correct (compare The peanut has to be under the cup versus the peanut might be under the box) and Chierchia and colleagues have shown that four-year-olds prefer stronger descriptions over weak ones when both options are valid (for example they choose all over some to describe a scenario that would best be described with all).…”
Section: Introductionmentioning
confidence: 99%